PENINGKATAN KEMAMPUAN GURU SEKOLAH DASAR MELALUI PELATIHAN PEMBUATAN MEDIA VIDEO PEMBELAJARAN INTERAKTIF MENGGUNAKAN MS POWER POINT - Bertha Bintari Wahyujati (Universitas Sanata Dharma, 2021)
Learning in schools during the COVID-19 pandemic requires changes in teaching methods which are adaptive to the conditions and situations of this pandemic. The boredom of students effected a decrease in understanding the concept of the learning materials. The way students tolearn and teachers to teach all this time must be change. The material must be delivered in order to attract children's interest in learning. From the survey results, most teachers only give assignments and materials using power point slides containing a lot of uninteresting texts and make children dependent on their parents to learn it. Therefore, Vocational lecturers of Sanata Dharma univercity as social community service team held training for teachers at Kanisius Sengkan Elementary School and Kalyca Elementary School to empower power point as software that they are already accustomed to using for teaching, transform it as a video learning media and interesting interactive learning evaluation which make children will be motivated to learn use video effectively and independent. After participating in this training, the teachers took the initiative to make their learning videos more interesting even though they only used MS Powerpoint software.